2015
DOI: 10.1007/s00415-015-7793-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer ratio in lesions rather than normal-appearing brain relates to disability in patients with multiple sclerosis

Abstract: Magnetization transfer ratio (MTR) is a semi-quantitative measure that seems to correlate with the degree of myelin loss and generally tissue destruction in multiple sclerosis (MS). Our objective was to comprehensively assess the MTR of lesions and normal appearing (NA) tissue separately in the white matter (WM), the cortex, the thalamus and the basal ganglia (BG) and determine their relative contribution to disability. In this cross-sectional study 71 patients were included (59 with relapsing-remitting MS, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…As low MTR values are associated with demyelination, this measure was expected to be altered in T2 lesions, but the independent relationship with disability in progressive MS is a novel finding (27,28). Our results therefore confirm and extend the results from a previous study in a combined cohort of patients with RRMS and SPMS, which reported reduced MTR values in white matter lesions and a non-significant trend to correlation with disability (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As low MTR values are associated with demyelination, this measure was expected to be altered in T2 lesions, but the independent relationship with disability in progressive MS is a novel finding (27,28). Our results therefore confirm and extend the results from a previous study in a combined cohort of patients with RRMS and SPMS, which reported reduced MTR values in white matter lesions and a non-significant trend to correlation with disability (21).…”
Section: Discussionsupporting
confidence: 92%
“…Despite this reservation, T2 lesions were reported to be associated with disability also in progressive MS (21,22). In the present study total T2 lesion volumes were consistently and comparably associated with disability assessed by 9HPT, T25FW, EDSS and PASAT scores.…”
Section: Discussioncontrasting
confidence: 53%
“…Whereas some studies have reported significant correlations between EDSS and MTR histogram features of normal-appearing brain tissue, 23,24 others have suggested that the MTR of lesions in white matter, rather than in normal-appearing tissue, relates to the disability in patients with MS. 4,25 Most important, correlations between MTR and clinical outcomes were predominantly detected for the highest EDSS (Ͼ3) scores. [25][26][27] Hence, the trend for a negative correlation of MTR in normalappearing tissue with the EDSS score (not significant) observed in our study is in agreement with these general findings. Overall, these controversial reports reflect confounding contributions to the standard MT signal induced by its sensitivity to multiple pathophysiologic mechanisms underlying MS, 28 which limits its ability to relate clinical deficits to underlying regional pathology.…”
Section: Discussionmentioning
confidence: 99%
“…MTR has been shown to be sensitive to demyelination in the cortex [81] and deep gray matter [82]. MTR from normal-appearing brain tissue has been associated with clinical disability [83], although a stronger clinical association of lesional MTR over normal-appearing tissue has been reported [84]. MRI is sensitive to water content and methods have been developed to identify water located between the lipid bilayers of myelin.…”
Section: Advanced Mri Methodsmentioning
confidence: 99%